Multifunctional Liposomes for Image‐Guided Intratumoral Chemo‐Phototherapy. Issue 16 (15th May 2017) - Miranda, Dyego; Carter, Kevin; Luo, Dandan; Shao, Shuai; Geng, Jumin; Li, Changning; Chitgupi, Upendra; Turowski, Steven G.; Li, Nasi; Atilla‐Gokcumen, G. Ekin; Spernyak, Joseph A.; Lovell, Jonathan F.
Abstract : Intratumoral (IT) drug injections reduce systemic toxicity, but delivered volumes and distribution can be inconsistent. To improve IT delivery paradigms, porphyrin–phospholipid (PoP) liposomes are passively loaded with three hydrophilic cargos: sulforhodamine B, a fluorophore; gadolinium‐gadopentetic acid, a magnetic resonance (MR) agent; and oxaliplatin, a colorectal cancer chemotherapeutic. Liposome composition is optimized so that cargo is retained in serum and storage, but is released in less than 1 min with exposure to near infrared light. Light‐triggered release occurs with PoP‐induced photooxidation of unsaturated lipids and all cargos release concurrently. In subcutaneous murine colorectal tumors, drainage of released cargo is delayed when laser treatment occurs 24 h after IT injection, at doses orders of magnitude lower than systemic ones. Delayed light‐triggering results in substantial tumor shrinkage relative to controls a week following treatment, although regrowth occurs subsequently. MR imaging reveals that over this time frame, pools of liposomes within the tumor migrate to adjacent regions, possibly leading to altered spatial distribution during triggered drug release. Although further characterization of cargo loading and release is required, this proof‐of‐principle study suggests that multimodal theranostic IT delivery approaches hold potential to both guide injections and interpret outcomes, in particular when combined with chemo‐phototherapy. Abstract : Porphyrin–phospholipid (PoP) liposomes are developed to load three hydrophilic cargo: a fluorophore for tracking cargo release; a magnetic resonance imaging agent for monitoring tumor distribution; and a chemotherapeutic. PoP liposomes rapidly release all cargos concurrently under near infrared light. Intratumoral injections are used to demonstrate chemo‐phototherapy under image guidance.